Ownership type, bank models, and bank performance: the case of the Yemeni banking sector - Fekri Ali Mohammed Shawtari (18069346) (2018)
Purpose The purpose of this paper is to examine bank performance using the different performance measures, namely, return on assets, return on equity and bank margins (MAR). Design/methodology/approach Unbalanced panel data were constructed to test the related hypotheses and provide evidence on the relationship between ownership types, banking models and performance indicators adopting the random effects techniques. Findings The findings of the paper substantiate that the banking models are significant performance indicators. However, the results are contingent on the GDP growth of the country. Moreover, the evidence indicates that the impact of ownership types is inconclusive in all measures of performance. However, the GDP is significant when it interacts with the types of ownership, particularly for foreign and government banks, although the evidence is mixed and unfavourable for government banks. Practical implications The results of the study provide insights for bankers and policymakers to enhancement Yemen’s banking sector. Originality/value This study is considered as the first attempt in examining the role of banking model and ownership type and their link to banking model. Other Information Published in: International Journal of Productivity and Performance Management License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1108/ijppm-01-2018-0029